Management of severe hidradenitis suppurativa with biologic therapy and wide excision - Lim, Shi Yu Derek (Arch Plast Surg, 2019)
Hidradenitis suppurativa (HS) is a chronic inflammatory follicular occlusive disease that involves the intertriginous areas. Treatment methods include conventional topical and systemic medication, radiotherapy, biologic agents, and surgical excision. Of late, there has been an increased focus on the use of biologic agents in patients with moderate to severe HS. Here, we present the case of a 46-year-old man with Hurley stage III HS for whom wide excision was ultimately curative, after aggressive medical therapy with the use of infliximab and adalimumab had succeeded in limiting the body surface area affected by the disease. This case demonstrates the effective treatment of severe HS with a combination of biologic therapy and surgery.